PrescripTech : Enhancing Healthcare Access through Generic Prescription Conversion - Jadhav, Shubham; Shetty, Rakesh; Gujare, Manoj; Prof. D. D. Sarpate (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
PrescripTech introduces a pioneering approach to healthcare access and affordability by converting brand-name conventions into original general druthers. Using sophisticated algorithms and integration with electronic health records (EHR), PrescripTech seamlessly analyzes patient data to recommend cost-effective drug options. This innovative platform addresses the pressing issue of drug affordability by promoting the use of generics, which offer similar efficacy at significantly lower costs. By easing cost-conscious prescribing practices, PrescripTech not only reduces fiscal burdens on cases but also contributes to the sustainability of healthcare systems worldwide. Also, PrescripTech has the implicit to profoundly impact healthcare access, particularly for underserved populations. By lowering drug costs, it ensures that essential treatments are accessible to individualities anyhow of their socioeconomic status. This democratization of healthcare aligns with broader pretensions of health equity and social justice, fostering positive issues for communities encyclopaedically. As a lamp of healthcare invention, PrescripTech exemplifies the transformative power of technology in optimizing healthcare delivery and advancing the principles of affordability and availability.